The Carnation Revolution from Spain in the archive of RTVE - García Varela, Pablo (2024)
Contemporary audio-visual sources offer us a  unique opportunity to learn about the key role of  television in the transmission of historical events  such as the Portuguese Carnation Revolution of 1974. The  objective of this article is to explain how TVE (Spanish Television) told the Spaniards about this  popular uprising in order to analyse the evolution of  the discourse of the public entity and Spanish society  from the end of the dictatorship to the  victory of the PSOE (Spanish Socialist Workers’ Party) in 1982.